Mcevoy's handbook of photovoltaics : fundamentals and applications - Kalogirou, Soteris (Academic Press, 2018)
Mcevoy's Handbook of Photovoltaics, Third Edition, is a benchmark publication for those involved in the design, manufacture and use of these devices. This fully revised handbook includes brand new sections on smart grids, net metering and the modeling of photovoltaic systems, as well as fully revised content on developments in photovoltaic applications, the economics of PV manufacturing and updated chapters on solar cell function, raw materials, photovoltaic standards, calibration and testing, all with new examples and case studies.
Keywords: Photovoltaic cells.; Photovoltaic power generation.; elektronické knihy; electronic books